Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.3847/1538-3881/ab4264
|View full text |Cite
|
Sign up to set email alerts
|

Photometry of the Uranian Satellites with Keck and the Search for Mab

Abstract: We present photometric properties of six small (radii < 100 km) satellites of Uranus based on 32 H -(1.49-1.78 µm) band images taken on August 29, 2015 from the Keck II Telescope on Maunakea, Hawaii with the near-infrared camera NIRC2 coupled to the adaptive optics system. The sub-observer latitude of our observations was 31 • , i.e., we view much of the satellites' north poles, in contrast to the 1986 Voyager measurements. We derive reflectivities based on mean-stacking measurements of these six minor moons o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 18 publications
(34 reference statements)
0
8
1
Order By: Relevance
“…Photometric datasets indicate that the ring moons are dark (except possibly Mab, Showalter & Lissauer 2006), with neutral spectral slopes and slight reductions in albedo at 1.5 and 2.0 µm, consistent with the presence of H 2 O ice (e.g., Karkoschka 2001). More recent photometric measurements indicate that the ring moons may display latitudinal variations in albedo, possibly resulting from interactions with Uranus' magnetosphere (Paradis et al 2019). Other photometric studies determined that Uranus' irregular satellites are dark and red (e.g., Grav et al 2004;Maris et al 2007), with possibly redder colors than the irregular satellites of the other giant planets (Graykowski & Jewitt 2018).…”
Section: Surface Compositions Of the Uranian Satellitesmentioning
confidence: 79%
“…Photometric datasets indicate that the ring moons are dark (except possibly Mab, Showalter & Lissauer 2006), with neutral spectral slopes and slight reductions in albedo at 1.5 and 2.0 µm, consistent with the presence of H 2 O ice (e.g., Karkoschka 2001). More recent photometric measurements indicate that the ring moons may display latitudinal variations in albedo, possibly resulting from interactions with Uranus' magnetosphere (Paradis et al 2019). Other photometric studies determined that Uranus' irregular satellites are dark and red (e.g., Grav et al 2004;Maris et al 2007), with possibly redder colors than the irregular satellites of the other giant planets (Graykowski & Jewitt 2018).…”
Section: Surface Compositions Of the Uranian Satellitesmentioning
confidence: 79%
“…The proper motion of Mab is roughly 30 mas (3 pixels) per minute, which means that each frame had to be shifted relative to the previous one in accordance with Mab's expected vector of motion to improve the signal-to-noise ratio (SNR). This so-called "shift-and-stack" technique has been used by other authors to improve the SNR of moving point sources, including to measure photometry of other small moons of Uranus with NIRC2 (Paradis et al 2019(Paradis et al , 2023. Our shift-and-stack procedure differs in several ways from the one implemented by those authors, and we describe it fully in Supplementary Material A.…”
Section: Observations and Data Processingmentioning
confidence: 99%
“…Those authors proposed two end-member cases: Mab has a ∼6 km radius with a Miranda-like icy surface and an albedo of ∼0.46, or Mab has a ∼12 km radius and an albedo of ∼0.1 like its other nearest neighbor, Puck. Previous near-infrared searches with Keck did not detect the moon; the upper limit of de Pater et al (2006) led to the suggestion that Mab was an icy body like Miranda, with substantial water-ice absorption, and the more sensitive upper limit of Paradis et al (2019) required that Mab's radius be ≲6 km and its surface as dark at 1.6 µm as Puck (albedo ≲0.11; Paradis et al 2023). Strong near-IR absorption from the crystalline water ice band at 1.65 µm is responsible for a factor-of-four darkening in the near-IR spectra of Pluto's outer satellites Nix and Hydra (Cook et al 2018), and this absorption band could explain such a low H-band flux.…”
Section: Introductionmentioning
confidence: 99%
“…In the case of Uranus, there is a moonlet, Mab, at the location of the μ-ring (Showalter and Lissauer 2006). However, Mab's radius is no more than 6 km (Paradis et al 2019), making geologic activity implausible. de Pater et al (2006) therefore suggested that the Uranian μ-ring may originate from micrometeorite impacts on Mab.…”
Section: Magnetospheric Influencing Of Ring Structure and Dynamicsmentioning
confidence: 99%